(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Amniotic membrane (AM) is widely used in ophthalmic surgery. There are three major techniques for amniotic membrane transplantation (AMT): ‘onlay’ (‘patch’) technique, ‘inlay’ (‘multilayer transplantation’) and ‘sandwitch’ technique (a combination of the two techniques mentioned before), but there is no universal technique for placing the amnion on the ocular surface for AMT. In conventional multilayer AMT, the membrane is fixed layer by layer with numerous interrupted sutures, which contributes to a severe corneal inflammatory response and the formation of intense corneal opacity. Purpose: To improve the multilayer amniotic membrane transplantation technique. Material and Methods: The method proposed by us consists in forming a two layer or three layer amniotic graft and anchoring it to the surrounding cornea by a row of interrupted 10-0 sutures. Twenty eight patients with corneal ulcers of different causes underwent amniotic membrane transplantation. There were 17 men (60.7%) and 11 women (39.3%). Mean patient age (standard deviation) was 51.3 (0.81) years. Corneal ulcers were categorized based on the etiology as herpetic (7/28, 25%), neurotrophic (10/28, 35.7%), bacterial (3/28, 10.7%), fungous (2/28, 7.2%), autoimmune (3/28, 10.7%) and those caused by rosacea (3/28, 10.7%). Results: After AMT by the proposed technique, there was a reduction in corneal stromal edema at discharge (χ2 = 29.7; p = 0.0005). In addition, corneal stromal infiltration resorbed at 1 month after surgery compared to at discharge (χ2 = 9.16; p = 0.0025). AMT by the proposed technique facilitated the formation of mild focal corneal opacity in 26 patients (92.8%). Conclusion: Our improved AMT technique reduces the number of sutures on the cornea, enables filling the corneal stromal defect and contributes to decreased inflammatory response and early epithelialization of the corneal surface.